Information systems adoption and knowledge performance: An absorptive capacity perspective - Liao, Huiyan; Liu, Yi; Li, Peigong (Frontiers in Psychology, 2023)
As strategic assets for organizations, information systems (IS) have been adopted to enhance organizational knowledge performance. Based on absorptive capacity perspective, we investigated intertwined relationships among IS adoption, organizational capabilities, IS-enabled absorptive capacity, and organizational knowledge performance. We empirically examined our model with survey data collected from 417 IS employees of 21 different state governments in United States. We find that: (1) IS adoption does not directly generate IS-enabled absorptive capacity; (2) organizational capabilities positively affect IS-enabled absorptive capacity; (3) synergies arising from complementarity between IS adoption and organizational capabilities have a positive impact on IS-enabled absorptive capacity; and (4) IS-enabled absorptive capacity significantly drives manager and employee knowledge performance. This research enriches the understanding of the relationship among IS adoption, organizational capabilities, and organizational knowledge performance in U.S. public sectors.